In-situ conservation of residual soil moisture through tillage and mulch for maize (Zea mays) in tropical Bay Islands - PRAMANIK, S C (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during dry season (December-April) of 1994-95 and 1995-96 to study theeffect of tillage (conventional and minimum) and mulching (rice straw, saw dust, coir dust and rice husk) on thegrowth, yield, moisture stress index and water use of maize (Zea mays L.) in the humid tropical climate of Bay Islands.The minimum tillage and conventional tillage were at par in respect of yield, crop growth and water-use. Among thevarious mulches, rice straw gave 52.11 % higher maize yield compared to the control. The yield increase was due tobetter crop growth parameters, improvement in moisture-stress indices, efficient root development, conservation ofmore amount of residual soil-moisture in the crop root zone and higher water-use efficiency. The coir dust and sawdust were next important materials bringing 47.59 and 46.77% higher maize yield than the unmulched plots.